Analyzing the Performance of Environmental Friendly Concrete That Contains Acid-Treated (H2SO4, H3PO4) Recycled Aggregate (International Journal of Innovative Research in Computer Science & Technology, 2023)
Its poor quality was one of the key  problems preventing recycled course aggregate (RCA)  from being used in concrete mixes. The quality of  recycled aggregate may be impacted by cement mortar on  the surface of the material. The examination of recycled  aggregate in various test results employing acid soaking  treatment procedures utilizing sulfuric acid and  phosphoric acid is the subject of this research. Natural  aggregate, recycled aggregate, recycled aggregate with  H2SO4 and recycled aggregate with H3PO4 are the four  types of concrete mixtures that are made. Using these  cleaned recycled aggregates in concrete has been proven  to be beneficial. The strength and durability of concrete  were also evaluated, and aggregate attributes were  computed. The test findings showed. The behavior of  recycled aggregate has changed according to the test  results after being treated with acid. Out of these two  acids, sulphuric acid treatment of recycled aggregates  produced the best results, followed by phosphoric acid  doing only marginally better. According to the overall  research, employing treated recycled aggregate in  concrete can significantly increase the strength and  durability properties of concrete made using recycled  aggregate.
Keywords: Recycled; Brobdingnag Ian